Chromatin regulation of somatic abiotic stress memory. (20th February 2020) - Bäurle, Isabel; Trindade, Inês
Abstract : This review summarizes recent findings on abiotic somatic stress memory with a focus on underlying chromatin and transcriptional mechanisms that have been unravelled in Arabdopsis thaliana . Abstract: In nature, plants are often subjected to periods of recurrent environmental stress that can strongly affect their development and productivity. To cope with these conditions, plants can remember a previous stress, which allows them to respond more efficiently to a subsequent stress, a phenomenon known as priming. This ability can be maintained at the somatic level for a few days or weeks after the stress is perceived, suggesting that plants can store information of a past stress during this recovery phase. While the immediate responses to a single stress event have been extensively studied, knowledge on priming effects and how stress memory is stored is still scarce. At the molecular level, memory of a past condition often involves changes in chromatin structure and organization, which may be maintained independently from transcription. In this review, we will summarize the most recent developments in the field and discuss how different levels of chromatin regulation contribute to priming and plant abiotic stress memory.